A review of Tersilochinae (Hymenoptera: Ichneumonidae) of Finland. Part 1: taxonomy - Khalaim, Andrey I.; Várkonyi, Gergely (Zootaxa, 2018)
The Tersilochinae fauna of Finland is critically revised (except subgenera Tersilochus Holmgren and Euporizon Horstmann). Tersilochinae in two principal Finnish ichneumonid collections, the Finnish Natural History Museum LUOMUS (University of Helsinki) and the private collection of R. Jussila (Turku), have been examined. Thirteen genera and 61 species are found to occur in Finland, including one new species, Barycnemis finnora Khalaim, sp. nov. The Nearctic genus Ctenophion Horstmann is recorded from Finland, as well as from the Palaearctic region, for the first time. Nineteen species are newly recorded from Finland and four species are excluded from the Finnish fauna. Barycnemis agilis (Holmgren) is transferred to the genus Spinolochus Horstmann (comb. nov.). Tersilochus sulcatus Hellén, 1958, a junior homonym of T. sulcatus Smith van Burgst, 1913, is synonymised with Phradis brevicornis Horstmann (syn. nov.). New data on distribution of 25 species in northwestern parts of Russia are also provided.